2014
DOI: 10.1177/1420326x13516656
|View full text |Cite
|
Sign up to set email alerts
|

Simulated comparative investigation of the daylight and airflow of the conventional Egyptian shutter ‘sheesh’ and a proposed latticework device ‘new mashrabiyya’

Abstract: Most urban and, recently, rural households in Egypt live in apartment buildings. Their faç ades typically consist of openings equipped with glass panels and wooden louvred shutters, known as sheesh.Although it blocks direct sunlight and ensures privacy, sheesh impedes entry of needed air and daylight and obstructs the view. In previous studies, a preliminary proposal concerning the replacement of the conventional sheesh has been presented. This paper reports the investigation that compared the daylight and air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Here the compromise is to offer sufficient privacy but with minimal restrictions on the benefits of windows such as daylight and ventilation. The mashrabiyya, a perforated wooden screen traditionally used in Middle Eastern nations, and wooden shutters have been examined in some studies of daylighting, ventilation and privacy [13][14][15] but traditional mashrabiyya are no longer a common choice. This paper reports an experiment conducted to investigate instead the privacy offered by two types of window treatments -horizontal blinds and frosted glass.…”
Section: Examining Female Visual Privacy As a Function Of Window Trea...mentioning
confidence: 99%
“…Here the compromise is to offer sufficient privacy but with minimal restrictions on the benefits of windows such as daylight and ventilation. The mashrabiyya, a perforated wooden screen traditionally used in Middle Eastern nations, and wooden shutters have been examined in some studies of daylighting, ventilation and privacy [13][14][15] but traditional mashrabiyya are no longer a common choice. This paper reports an experiment conducted to investigate instead the privacy offered by two types of window treatments -horizontal blinds and frosted glass.…”
Section: Examining Female Visual Privacy As a Function Of Window Trea...mentioning
confidence: 99%
“…[73] The study provides an approach to integrate Biomimicry techniques and the historical architecture to reach applications that enhance sustainability Arab world Ramzy, (2015). [74] The study presents a development of the idea of the traditional Mashrabiyya and comparing it to the prevailing windows in Egypt, known as Sheesh.…”
Section: Arab World Abdelsalam and Rihan (2013)mentioning
confidence: 99%
“…Conversely, Aljofi [19] confirmed that the critical assessment of Rawshan thermal output, with its natural ventilation capacity, should always be pursued to produce environmentally sensitive screens of the Rawshan. On the other hand, Gelil M and Badawy [20] prevented the revival of the Rawshan's (Mashrabiyyah) screen in countries such as Egypt due to air pollution. Nevertheless, the ventilation factor seems to be perceived as a limitation in the Western Region of Saudi Arabia (Hedjaz) as discussed in Chapter 5, Section 5.3.2.…”
Section: Literature Reviewmentioning
confidence: 99%